ระบบบริหารความต้องการการขนส่งสินค้า สำหรับอุตสาหกรรมเครื่องนุ่งห่ม - เดชโรจน์ ตั้งสิน (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The objective of this research is to develop a management system of transportation requirement for a garment industry. The system will increase the efficiency of transportation communication and resources. It covers collecting data of factors affecting transportation date and time, communication of transport schedule, and communication of transportation results. The research procedure consists of surveying the process of transportation and the process of generating transportation plan, studying the previous research, designing the transportation requirement system, and evaluating the system by interviewing people whose works are related to transportation in the industry. The outputs of this research are concept and procedure for a system of transportation requirement management in the forms of business process charts, logic and process for transportation requirement decisions, process for communicating data on transportation time, and computer screens for every work process. The results of this research will improve the communication of the officers involved in transportation, and will improve transportation planning, which will increase the efficiency of the communication and transportation resource.